Pengaruh Perbedaan Bahan Pengikat yang dikombinasikan dengan Bahan Penghancur dalam SediaanTabletHisap Ekstrak Habbatus Sauda' (Nigella sativa L.) - Anugerah Suciati; Andi Sri Suriati Amal; Lija Oktya Artanti (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2019)
Habbatus sauda ' (Nigella sativa L.) have been examined have the content of flavonoid compounds that act as antioxidants. In order to be utilized more effectively and efficiently, it needs to be made innovation preparations with active substances habbatus sauda '. One of the innovations of preparations that can apply habbatus sauda ' as the active substance is troches. This research was conducted to find out the influence incurred due to the difference in binders combined with disintegrant on troches dosage habbatus sauda' extract. Binders used are amylum manihot and PVP while disintegrant used is Avicel PH 102. Troches’ made in four different formulas. The method used in the manufacture of troches is wet granulation with 70% ethanol spraying. On the stage of preformulation, carried out an analysis of halal ingredients. The analysis shows the critical point of halal ingredients used in the formulation is not found. The results of the evaluation of physical properties of granule and tablet indicates that the difference in binders combined with disintegrant affect the physical properties of granule and tablet. The best formula is the Formula 3 with an average value of hardness 8,69 kg/cm3 and the fragility of 0,54%.